Relationship between job satisfaction and work performance : a case study of Sarikei Hospital, Sarawak - Lu, Chan Woon (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Purpose The main purpose of this study was to determine the relationships between job satisfaction and work performance among 20 1 support group personnel in Sarikei Hospital, sarawa.,0 Methodology - Questionnaires consisted of three parts were distributed to all the support group of staff in Sarikei Hospital. The first part of the questionnaire is analyzing the demographic of respondents and the gender of their supervisors. The next two parts are attached with 36 and 20 questions respectively reflected each individual dimensions of job satisfaction and work performance. The data was analyzed by the SPSS Version 17.0 computer software. Findings - It was found that work and communication are significantly related to client satisfaction with ~ = .39 with p < 0.0 I and .17 with p < .05 respectively. As for employee satisfaction, only work is significantly related to it with ~ = .62 with p < 0.0 I. However, benefits and communication are found to be significantly related to productivity with ~ = .18 with p < 0.05 and .18 with p < 0.05 respectively. It was found that supervision and work are significantly related to service quality with .~ = .18 with p < 0.05 and .27 with p < 0.01 respectively. Research limitations/practical implications - In this study, employees' participation was voluntary and was conducted to the support group I only. These factors limit the possibility of generalizing from the study findings. This study may serve as a foundation for future studies, in different hospitals, on a larger scales. The results of such studies can be very helpful for developing a new model of job iii satisfaction and work performance that can be implemented easily and successfully in a cross cultural context in the public services in Malaysia.